Exploriso : Low-tech Fine art / : Risography as an artistic printing process - Tillack, Sven (Leipzig : Spector Books, 2020)
bijlage: Exploriso Colour Suite: Tiziana Jill Beck ; Blexbolex ; It's Raining Elephants ; Maja Behrmann ; Ben El Halawany ; Hansje Van Halem ; Pooroni Rhee ; Lea Dohle ; Zoran Pungercar ; Christoph Feist ; Stefan Marx ; Hyojoon Jo ; Raby-Florence Fofana ; Dr. Alderete ; Kati Szilagyi ; etc.
boek